重构软实力 ：论中国如何在东南亚运用实力资源元素发展软实力 = Recomposing soft power : a discussion of how China utilizes power resource elements to develop its soft power in Southeast Asia - 薛文豪 Seet, Wen Hao (2010)
软实力研究框架的出台，为普遍只以一国的军事力量或经济力量等硬实力资源元素作为衡量国家实力的标准，提供了全新的模式。而中国在近年来似乎也接纳了软实力研究框架的概念，在对外展现国家实力之时，也由“硬转软”，逐渐注重自身的软实力本质发展。虽然说研究框架的确为国家实力的认识打开了新的局面，但其研究框架却也存在着瑕疵。本文将通过对研究框架进行深入探讨，以中国如何在东南亚运用实力资源元素发展软实力本质的实践为案例，论述并凸现研究框架所存有的不足之处。最后，本文将以所提出的研究案例作为基础，在点明出研究框架当中的不足后，为研究框架进行适当的修正，以完善当中的不全。 The introduction of the soft power research framework has provided a new research model for measuring national power. This framework is in contrast with the usual scale of using military, economic or other hard power resources elements as a measure of national power. In recent years, China seemed to have accepted the concept of soft power research framework. China’s external display of national power has gradually changed from focusing on hard power to the development of its soft power. Although the research framework has opened up new doors in understanding of national power, there are also flaws within it. This paper will study the research framework via an in-depth discussion of a case study on how China utilizes its power resource elements to develop its soft power in Southeast Asia. This discussion will shed light on the shortcomings of the research framework.